THE PATHOGENETIC SIGNIFICANCE OF HEMOSTASIS DISORDERS DETECTION FOR THE DIAGNOSTICS AND PREVENTION OF THROMBOTIC COMPLICATIONS IN WOMEN WITH ANTENATAL FETAL DEATH - Kotenok , Antonina; Hychka, Nazariy; Beniuk , Vasyіl (The Ukrainian Scientific Medical Youth Journal, 2019)
The article summarizes the arguments and counterarguments within the scientific debate on the diagnosis and prevention of disorders in hemostatic blood system in women with antenatal fetal death. The main purpose of this investigation is to study the changes in the hemostatic system in pregnant women with antenatal fetal death, namely to evaluate the features of procoagulant, anticoagulant and fibrinolytic units of the hemostatic system in women with antenatal fetal death. The systematization of literary sources and approaches to the problem of hemostatic disorders in antenatal fetal death provides an opportunity to confirm the importance of this issue, to reasonably evaluate the risks during pregnancy in each particular woman and, first of all, to prevent the occurrence of this complication. This article presents the results of a retrospective study of individual case histories of pregnant women and the case histories of childbirth of women with antenatal fetal death and physiological pregnancy in the period from 2016 to 2018. The relevance of the study of this pathology is that every fifth woman of reproductive age faces a problem such as perinatal loss. In the structure of perinatal losses, antenatal fetal death occupies a special place, which can lead to the development of fetal loss syndrome, DIC, infectious complications in the mother and infertility or subfertility in the future, which in general has a negative impact on the reproductive potential of the nation. In the course of our work we evaluated such coagulogram indicators as: prothrombin index, thrombin time, activated partial thrombin time, soluble fibrin monomer complexes, plasma fibrinogen, antithrombin III, and protein C. It is established that pregnant women with antenatal fetal death are characterized by increased blood clotting activity against the background of suppression of anticoagulant and fibrinolytic units of hemostasis. Determination of the activity of antithrombin III informs about the state of anticoagulation system of the body and provides an opportunity to adjust the treatment with anticoagulant drugs of direct action. Indicators of coagulogram canʼt fully reflect the state of hemostasis during pregnancy, so the search for new methods of early diagnosis of imbalance in the system of hemostasis during pregnancy remains relevant at this stage. These studies may be useful for gynecologists, especially in women's counseling, for the formation of risk groups for pregnant women and for preventive measures to prevent antenatal fetal death.